Enhancing Good Corporate Governance to Shape the Impact of Corporate Internet Reporting and Green Accounting on Firm Value: Evidence of Energy Companies in Indonesia - Citrawati Jatiningrum; Murni Indah Sari; Azli Fahrizal; Iing Lukman (Moneter: Jurnal Keuangan dan Perbankan, 2026)
This study aims to examine the effect of Corporate Internet Reporting (CIR) and Green Accounting (GA) on firm value, with Good Corporate Governance (GCG) serving as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange. The study adopts a quantitative research design using secondary data derived from annual reports, sustainability reports, and corporate governance disclosures. The sample was determined through purposive sampling, and the data were analyzed using Moderated Regression Analysis (MRA). The findings reveal that Corporate Internet Reporting has a significant negative effect on firm value, whereas Green Accounting has a significant positive effect on firm value. Furthermore, the main finding of this study is that Good Corporate Governance moderates the relationship between Corporate Internet Reporting and Green Accounting and firm value. These findings suggest that effective corporate governance enhances the credibility and usefulness of corporate disclosures and strengthens environmental accounting practices. Evidence also indicates that energy sector companies need to improve the quality of Corporate Internet Reporting, consistently implement Green Accounting, and strengthen risk management and the implementation of Good Corporate Governance to increase investor confidence and Firm Value.